Territorialidades no espaço público urbano : uma análise de praças na cidade de Vitória (ES) - Tostes, Taís Rodrigues de Souza (2017)
This paper aims to record and discuss the role of territorialities in possible appropriations of public spaces, as well as the relations between inhabitant and such spaces, the fundamental concepts for such adjustments. The choice of the public space as o